Continuous production of cellular ceramics through thermoplastic foam extrusion - Forstner, Thomas; Drummer, Dietmar (SPE ANTEC 2024, 2024)

Enhanced Feedstock Processability for the Indirect Additive Manufacturing of Metals by Material Extrusion through Ethylene–Propylene Copolymer Modification - Forstner, Thomas; Cholewa, Simon; Drummer, Dietmar (Polymers, 2024)

Influence of wax addition on feedstock processing behavior in additive manufacturing of metals by material extrusion - Forstner, Thomas; Cholewa, Simon; Drummer, Dietmar (Progress in Additive Manufacturing, 2024)

Modification of foam morphology in powder extrusion molding of alumina with thermally expandable microspheres - Forstner, Thomas; Drummer, Dietmar (MSE 2024 - Materials Science and Engineering Congress, 2024)
The indirect manufacturing technologies of powder injection molding (PIM) or powder extrusion molding (PEM) are promising ways for the efficient production of complex, near-net-shape metal or ceramic parts. These special processes, which combine the geometric flexibility and efficiency of polymer technology with the desired final properties of specific metals or ceramics after sintering, already address manifold applications throughout industry, the medical sector or everyday life. However, this variety can be further expanded via a combination of these processes with other techniques from polymer technology, such as chemical or physical foaming, which are commonly used to produce lightweight polymer foam materials. For this study, thermally expandable microspheres (TEM) were used within the continuous PEM process for the creation of cellular ceramic profiles with tailorable foam properties in a multi-step-process. Therefore, a highly filled polymer feedstock was processed with rising TEM-contents and varying screw speeds. The extruded profiles were evaluated regarding their pore morphologies and densities in their green and sintered states via sub-µ-computed tomography (sub-µ-CT). The amount of TEM’s added was found to directly influence the porosity of the green and sintered part, allowing a tailorable porosity as Figure 1 demonstrates. Furthermore, the pore morphology given by the templates in the green state also manifests in the sintered state, leading to porosities of up to 37 % within the sintered par

Polybutylene terephthalate for laser-based powder bed fusion of polymers: processing constraints driven by zero-shear viscosity - Cholewa, Simon; Forstner, Thomas; Jaksch, Andreas; Drummer, Dietmar (Progress in Additive Manufacturing, 2025)
Laser-based powder bed fusion of polymers (PBF-LB/P) is a layer-based additive manufacturing (AM) method that produces functional components with superior mechanical properties. However, the limitation of commercially available materials, primarily polyamides, reduces the range of applications for PBF-LB/P processed parts. The use of novel polymer feedstocks, such as polybutylene terephthalate (PBT) in PBF-LB/P is of great interest, as the properties of PBT allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Studies on the flowability of the powder under process conditions at evaluated temperatures showed a homogeneous surface of the powder bed. In addition, the processability of PBT powders in the PBF-LB/P process was investigated with a thermal camera, showing process limits for low-viscosity materials. Component properties showed a higher Young’s modulus than injection molding, while fracture behavior showed brittle behavior for the homo-PBT tested.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Additive manufacturing; Balling; Morphology; Powder bed fusion; Zero-shear viscosity

Understanding chemical foaming of highly filled ceramic feedstocks for injection molding - Forstner, Thomas; Drummer, Dietmar (PROCEEDINGS OF THE 38TH INTERNATIONAL CONFERENCE OF THE POLYMER PROCESSING SOCIETY (PPS-38), 2024)

β-Modification in heterogeneous polypropylene for laser-based powder bed fusion of polymers - Cholewa, Simon; Forstner, Thomas; Drummer, Dietmar (Progress in Additive Manufacturing, 2024)